Microplastic abundance, distribution and composition along a latitudinal gradient in the Atlantic Ocean. (15th February 2017) - Kanhai, La Daana K.; Officer, Rick; Lyashevska, Olga; Thompson, Richard C.; O'Connor, Ian
Abstract: Microplastics in the world's oceans are a global concern due to the potential threat they pose to marine organisms. This study investigated microplastic abundance, distribution and composition in the Atlantic Ocean on a transect from the Bay of Biscay to Cape Town, South Africa. Microplastics were sampled from sub-surface waters using the underway system of the RV Polarstern . Potential microplastics were isolated from samples and FT-IR spectroscopy was used to identify polymer types. Of the particles analysed, 63% were rayon and 37% were synthetic polymers. The majority of microplastics were identified as polyesters (49%) and blends of polyamide or acrylic/polyester (43%). Overall, fibres (94%) were predominant. Average microplastic abundance in the Atlantic Ocean was 1.15 ± 1.45 particles m − 3 . Of the 76 samples, 14 were from the Benguela upwelling and there was no statistically significant difference in microplastic abundance between upwelled and non-upwelled sites. Highlights: Average microplastic abundance in sub-surface waters of the Atlantic Ocean was 1.15 particles m − 3 . Of the microplastics, polyester and blends of polyamide or acrylic/polyester were most abundant. The predominant type of microplastics was fibres. Microplastic abundance at Benguela upwelling and non-upwelled sites not statistically different